Towards a new architecture for the euro area: An early appraisal of the Juncker Commission - Christoph Bierbrauer (Osnabrück University, Institute of Empirical Economic Research, 2020)
We provide an early assessment of the Juncker Commission's contributions to the ongoing reform of the euro area. In doing so, we present a chronological summary of the reform process up to 2014. At the time, the euro area architecture had undergone many changes. These were mainly focused on risk prevention in the tradition of the original Stability and Growth Pact. The self-proclaimed priority of Juncker was the translation of already agreed upon reforms into European law and to add mechanisms for risk sharing in the public and private sector. Other objectives included kick-starting investment in Europe, increase transparency and democratic accountability and to make the workings of the Commission more visible to improve public support for the common institution. The Juncker Commission faced a Sisyphean task. A slow bur steady euro areawide economic upturn, positive for member states, eased their economic pressures and led to a general reform fatigue. Moreover, the Brexit decision in the United Kingdom absorbed resources as well as attention and made reform decisions that require unanimity among the member states difficult. In Juncker's term, reforms moved at glacial speed, a major breakthrough with regard to adding risk sharing to the euro area architecture could not be achieved. In his term however, the Commission was able to provide considerable support for investment in Europe and to increase public support for the European project which was at a record low when Juncker took office.
Keywords: E00; E02; E69; F36; F45; F53; F59; H00; H12; 330; European Union; European Economic and Monetary Union; EuropeanCommission; Jean-Claude Juncker; Euro area reform; European Integration; Europeandebt crisis; Public Debt; Decentralized scal policy; Monetary union